Cross-sectional and prospective relationships of endogenous progestogens and estrogens with glucose metabolism in men and women: A KORA F4/FF4 Study - Lau, Lina Hui Ying (BMJ Publishing Group, 2022)
10.1136/bmjdrc-2020-001951